Informality and exclusion: Evidence from matched employer-employee data for Lebanon and Syria - Mohamad Alloush; Carole Chartouni; Roberta Gatti; Joana Silva (IZA Journal of Labor Policy, 2013)
Informality, measured as the share of the employed who do not have access to social security, is high in Lebanon and the Syrian Arab Republic. This paper uses new data from the 2010 Lebanon and Syria matched employer-employee surveys, which include modules that directly test for ability (Raven's progressive matrices) and self-reported personality characteristics in addition to a detailed section on job quality. The analysis of differentials in earning, self-reported attitudes toward jobs, working conditions, and self-rated satisfaction across formal and informal jobs shows that, even after controlling for measured ability and personality traits, there is a significant formality premium. Moreover, in Lebanon, informal workers are significantly more likely than formal workers to want to change jobs. These findings suggest that much of the observed informality in these two countries might not be due to individual choice but more likely to exclusion from formal markets.
Keywords: H53; H55; J23; J24; J31; J32; J42; J71; J81; K31; M51; O53; 330